Vocational education and training in Sweden : short description - (:unkn) unknown (Publications Office of the European Union, 2009)
This overview of vocational education and training (VET) in Sweden has been produced to mark Sweden's Presidency of the Council of the EU. It forms part of the series of short descriptions regularly published by Cedefop on national VET systems. "Vocational education and training in Sweden is in the midst of a series of major reforms to ensure labour market relevance and increase quality. The current system of integrated upper secondary education will be replaced in 2011 by a system with three broad orientations: (a) general education, mainly for those intending to pursue higher education; (b) school-based vocational programmes; and (c) work-based apprenticeship. The new upper secondary system will ensure that VET students acquire more vocationally specific knowledge and skills while retaining a strong theoretical core. Another major VET reform is creation of the new Agency for Higher Vocational Education (Yrkeshögskolan) on 1 July, 2009. The new agency will bring together postsecondary VET types under one administrative structure, apply more robust quality assurance procedures and ensure that vocational education and training more closely meets labour market skill needs." (Hrsg., BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; I 2.2.1 Westeuropa; Berufsbildungssystem; Bildungspolitik; Berufsbildendes Schulwesen; Berufliche Weiterbildung; Bildungspersonal; Berufliche Qualifikation; Anerkennung; Informelles Lernen; Berufsberatung; Bildungsfinanzierung; Schweden